A study of adherence of drug promotional literatures from various clinical specialties to the World Health Organization ethical criteria for drug promotion (Journal of Pharmaceutical Negative Results, 2016)
Introduction: Doctors‑prescribing practices are influenced by drug promotionalactivities. Studies have shown that drug promotional literatures (DPLs) do not conformto the established regulations in many countries. However, whether the non-conformanceis more likely in a particular clinical specialty needs to be determined. The objective ofour study was to assess the adherence of DPLs sampled from various clinical specialtiesto the World Health Organization (WHO) criteria for ethical drug promotion anddetermine the presence of any difference. Methodology: Thirty DPLs were collectedfrom each of the five clinical specialty clinics (General Medicine, Surgery, Obstetricsand Gynecology, Pediatrics and Psychiatry) of a University Teaching Hospital. Eachpromotional literature was evaluated for adherence to the individual WHO ethicalcriteria’s for drug promotion. Results: More than 80% of the promotional literaturesfrom all the clinical specialties did not contain information on dosage modification,contraindications, precautions, adverse effects, drug interactions, drug over dosage,excipients, storage and shelf‑life, and legal category of the drugs. Nearly 19.33%of the DPL were for vitamins, minerals, and nutritional supplements; 13.33% forantimicrobials and 10% for anti‑anxiety medications. Conclusions: Our study showsthat most of the DPLs across clinical specialties failed to adhere to many of the WHOcriteria of ethical drug promotion. The information lacking in the DPLs is critical forrational decision making. Considering that these irregularities are present across clinicalspecialties, it is important to strengthen the regulations governing drug promotion.